Selected work-related nephropathies - Wojciech Wołyniec; Marcin Renke; Małgorzata Wójcik-Stasiak; Joanna Renke (Nofer Institute of Occupational Medicine, 2015)
Infections, high temperature and many of the toxic substances can cause kidney damage. Acute kidney injury is a well known complication of some work-related diseases, e.g., lead intoxication. Chronic kidney disease can also be caused by some occupational factors. Three work-related nephropathies, in which causal connection with work has been proved, are discussed in this article. There are different risk factors of nephrolithiasis, lead nephropathy and silica nephropathy, but each of them can cause chronic kidney disease. Prevention of these nephropaties seems to be relatively simple. The principles of protection from the toxic effects of heavy metals and silica dust are very specific. The most important prevention of kidney stones is correct fluid intake. In addition to providing adequate quantities of drinking water, it is also important to educate exposed workers and assure enough rest breaks at work. Med Pr 2015;66(4):583-593